![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
\(x-\dfrac{20}{11\cdot13}-\dfrac{20}{13\cdot15}-...-\dfrac{20}{53\cdot55}=\dfrac{3}{11}\)
\(\Leftrightarrow x-10\left(\dfrac{2}{11\cdot13}+\dfrac{2}{13\cdot15}+...+\dfrac{2}{53\cdot55}\right)=\dfrac{3}{11}\)
\(\Leftrightarrow x-10\left(\dfrac{1}{11}-\dfrac{1}{13}+\dfrac{1}{13}-\dfrac{1}{15}+...+\dfrac{1}{53}-\dfrac{1}{55}\right)=\dfrac{3}{11}\)
\(\Leftrightarrow x-10\cdot\dfrac{4}{55}=\dfrac{3}{11}\)
hay x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: 1 + 5 + 6 = 12 ; 2 + 3 + 7 = 12
Vậy 1 + 5 + 6 = 2 + 3 + 7
b) Ta có:\(1^2\)\(+5^2\)\(+6^2\)\(=1+25+36=62\)
\(2^2\)\(+4^2\)\(+7^2\)\(=4+16+49=62\)
\(=>1^2\)\(+5^2\)\(+6^2\)\(=2^2\)\(+3^2\)\(+7^2\)
c) Ta có 1 + 6 +8 = 15; 2 + 4 + 9 = 15
Vậy 1 + 6 + 8 = 2 + 4 + 9
\(d,1^2\)\(+6^2\)\(+8^2\)\(=1+36+64=101\)
\(2^2\)\(+4^2\)\(+9^2\)\(=4+16+81=101\)
\(1^2\)\(+6^2\)\(+8^2\)\(=2^2\)\(+4^2\)\(+9^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x+1+x+2+x+3+x+4+x+5+x+6+x+7+x+8+x+9+x+10=5
(x+x+x+x+x+x+x+x+x+x)+(1+2+3+4+5+6+7+8+9+10)=5
10x+55=5
10x=55-5
10x=50
x=50:10
x=5
(x+1)+(x+2)+(x+3)+....+(x+10)=5
(x+x+x+x+x+x+x+x+x+x)+(1+2+3+...+10)=5
10x +55=5
10x=5-55
10x=-50
x=-50:10
x=-5
k nha
![](https://rs.olm.vn/images/avt/0.png?1311)
b)\(\frac{11}{4}:\left(2.y+\frac{5}{7}\right)=\frac{1}{2}\)
\(\left(2.y+\frac{5}{7}\right)=\frac{11}{4}:\frac{1}{2}\)
\(\left(2.y+\frac{5}{7}\right)=\frac{11}{2}\)
\(2y=\frac{67}{14}\)
\(y=\frac{67}{28}\)
Vậy \(y=\frac{67}{28}\)
\(\frac{11}{4}:\left(2y+\frac{5}{7}\right)=\frac{1}{2}\)
<=> \(\left(2y+\frac{5}{7}\right)=\frac{11}{4}:\frac{1}{2}=\frac{11}{4}.2=\frac{11}{2}\)
<=> \(2y=\frac{11}{2}-\frac{5}{7}=\frac{67}{14}\)
<=> y = 67/28
Chúc bạn làm bài tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
1+2+3-4-5-6+...+97+98+99-100-101-102
= (1+2+3-4-5-6)+...+(97+98+99+100+101+102)
= (-3)+...+(-3) (có 17 số -3)
= (-3)×17
=-51
( 6-x ) + (-11) = - 7
<=>6-x=(-7)-(-11)
<=>6-x=4
<=>x=6-4
<=>x=2
Vậy x=2